PERAN WORK PASSION DAN JOB CRAFTING DALAM MENINGKATKAN KINERJA GURU SEKOLAH DASAR: STUDI EMPIRIS - Afrizal, Afrizal; Wazirman, Wazirman (Jurnal Manajemen Pendidikan, 2026)
Teacher performance remains a critical issue in improving education quality, particularly at the primary school level, which faces increasing professional demands and limited resources. This condition indicates that performance is influenced not only by structural factors but also by teachers’ psychological factors and adaptive behaviors. This study aims to examine the effect of work passion and job crafting on primary school teachers’ performance. This study employed a quantitative approach with an explanatory survey design. The sample consisted of 69 public primary school teachers in Siulak District, Kerinci Regency, selected using a census sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression. The results reveal that work passion and job crafting have a positive and significant effect on teacher performance, both partially and simultaneously. Job crafting shows a more dominant influence. Together, both variables contribute 51.8% to teacher performance. This study highlights the integration of work passion and job crafting in explaining teacher performance in a rural primary education context. It suggests that schools should support teachers in developing adaptive work behaviors through training, innovation, and flexible work environments.